Strange features are no better than no features: predator recognition by untrained birds - Ondřej Fišer; Irena Strnadová; Petr Veselý; Michaela Syrová; Michal Němec; Barbora Kamišová; Josef Šalom; Roman Fuchs (Animal Cognition)
Abstract Predator recognition is essential for prey survival, allowing for appropriate antipredator strategies. Some bird species, such as the red-backed shrike (Lanius collurio), distinguish not only between predators and non-threatening species but also between different predator species. Earlier studies have identified general predator “key features”, especially beak shape and talons, as critical for predator recognition. The question, though, still remains of whether exchanging predator key features with those of nonpredatory species or, alternatively, completely removing them, have different or equal impact on recognition. Here we tested to ascertain whether the presence of the “incorrect key features” of a harmless pigeon (Columba livia) placed on a common kestrel (Falco tinnunculus) body impairs predator recognition more efficiently than the absence of any key features. We presented an unmodified kestrel dummy and two modified kestrel dummies (one with pigeon key features, the other lacking key features) to wild red-backed shrikes defending their nest. The shrikes attacked the unmodified dummy kestrel more intensively than both kestrel modifications when defending the nest. However, shrikes did not show different responses to the kestrel with pigeon key features and the featureless kestrel. Our findings show that the absence and exchange of key features have the same effect in this case. These results are discussed in the context of recognition of a specific predator species and predators as a category in general.